2022
DOI: 10.3390/jcm11092475
|View full text |Cite
|
Sign up to set email alerts
|

FGFR Fusions as an Acquired Resistance Mechanism Following Treatment with Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors (EGFR TKIs) and a Suggested Novel Target in Advanced Non-Small Cell Lung Cancer (aNSCLC)

Abstract: Background. FGFR1/2/3 fusions have been reported infrequently in aNSCLC, including as a rare, acquired resistance mechanism following treatment with EGFR TKIs. Data regarding their prevalence and therapeutic implications are limited. Methods. The Guardant Health (GH) electronic database (ED) was evaluated for cases of aNSCLC and FGFR2/3 fusions; FGFR2/3 fusion prevalence with and without a co-existing EGFR mutation was assessed. The ED of Tel-Aviv Sourasky Medical Center (TASMC, June 2020–June 2021) was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This combination treatment was tolerable for the mice and induced marked shrinkage of H3122 LR3 tumor (Figure 4C). In addition to FGFR abnormalities described above, recent studies revealed that FGFR fusion proteins can induce resistance to EGFR TKIs 46,47 . Therefore, we analyzed the existence of FGFR3 fusion protein in H3122 LR3 cells, but no FGFR3 fusion proteins were detected.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This combination treatment was tolerable for the mice and induced marked shrinkage of H3122 LR3 tumor (Figure 4C). In addition to FGFR abnormalities described above, recent studies revealed that FGFR fusion proteins can induce resistance to EGFR TKIs 46,47 . Therefore, we analyzed the existence of FGFR3 fusion protein in H3122 LR3 cells, but no FGFR3 fusion proteins were detected.…”
Section: Discussionmentioning
confidence: 92%
“…In addition to FGFR abnormalities described above, recent studies revealed that FGFR fusion proteins can induce resistance to EGFR TKIs. 46 , 47 Therefore, we analyzed the existence of FGFR3 fusion protein in H3122 LR3 cells, but no FGFR3 fusion proteins were detected. However, this result does not preclude the possibility that FGFR3 fusion can induce resistance to ALK TKIs.…”
Section: Discussionmentioning
confidence: 99%
“…The high expression/fusion of FGFR1 increases tumorigenicity and resistance to EGFR-TKI in EGFR mutant lung adenocarcinoma cells, which can be reversed by the dual inhibition of EGFR and FGFR. 270 , 271 The combination of EGFR and FGFR inhibitors reverses EGFR resistance mediated by downstream PIK3CA activation in skin squamous cell carcinoma. 272 Interactively, EGFR-dependent signal transduction induces resistance to FGFR inhibitors in head and neck squamous cell carcinoma cells with high expression of FGFR1 and cholangiocarcinoma cells with FGFR2 fusion.…”
Section: Development: Excavating Therapeutic Potential According To N...mentioning
confidence: 99%
“…FGFR3-TACC3 fusions account for over 91% of them, while fusions co-occurred with EGFR mutations in roughly 24% of cases. Among 3 patients with FGFR3-TACC3 fusions as resistance mechanisms to EGFR TKIs, two were treated with an EGFR TKI with the FGFR TKI, erdafitinib, with a 6 and 13 month response [ 264 ]. These results highlight the complexity of FGFR alterations.…”
Section: Ros1mentioning
confidence: 99%